IMPROVING STUDENT'S ABILITY IN WRITING RECOUNT TEXT THROUGH ROLE AUDIENCE FORMAT TOPIC (RAFT) STRATEGY - Fitriana, Fitriana; Rosdiana, Rosdiana; Mulyani, Mulyani (Jurnal Ilmiah Mahasiswa Pendidikan, 2024)
This Study aims to find out the relevance of adopting the RAFT strategy to improve students' writing abilities in recount text at SMA 2 Kutablang. This research used quantitative design with experimental. The instrument in this research was Test. The participant in this research were 26 tenth grade students of SMAN 2 Kuta Blang. The study focused on evaluating the effectiveness of RAFT (Role, Audience, Format, and Topic) strategies in enhancing students' recount text writing skills. The initial analysis of pre-test scores revealed that students exhibited poor writing skills, particularly in recount texts, characterized by issues in vocabulary, structure, coherence, and mechanical errors. Upon implementing the RAFT strategy, a remarkable improvement was observed, with the average student score increasing from 49 to 78.36. The findings underscored that the RAFT strategy not only positively influenced students' writing skills but also heightened their enthusiasm and engagement in the learning process. Students displayed enhanced imagination, motivation, and willingness to express ideas, contributing to the development of well-crafted recount texts. The strategy addresses various aspects of writing, including content, grammar, structure, vocabulary, and mechanics. By mitigating boredom and fostering active participation, the RAFT strategy emerges as a meaningful and practical approach in the teaching and learning of writing skills, contributing positively to the overall English education curriculum.